Continuity and Change in Islamic Law: Debates Among Nahdlatul Ulama Scholars on Misyār Marriage and Its Legal Dynamics in East Java - Nasiri, Nasiri; Sahri, Sahri; Mutmainah, Mutmainah; Khalil, Muhammad Amin; Ramadhan, Ahmad Fadhail (Journal of Islamic Law, 2025)
Misyār marriage constitutes one of the most contentious issues in contemporary Islamic legal discourse. Although it is formally recognized as valid, it raises significant social and ethical challenges. Previous research has primarily focused on the legality of misyār marriage within fiqh (Islamic jurisprudence), state regulations, or public responses. This article addresses a gap in the literature by examining how religious scholars affiliated with Nahdlatul Ulama (NU) in East Java negotiate normative texts, scholarly traditions, and social realities in their responses to this phenomenon. Employing a socio-legal framework, the study draws on semi-structured interviews with 14 key informants, non-participant observations within four residential communities in Surabaya, and document analysis of classical fiqh texts alongside marriage archives. The findings identify three principal models of misyār marriage in Surabaya: as a strategy utilized by career women, as short-term unions designed to circumvent bureaucratic complexities, and as transnational marriages involving foreign men. These practices are motivated not solely by biological needs but also by economic, social, and cultural factors. The responses of NU religious scholars coalesce into two main orientations: cultural scholars, who emphasize the contractual validity based on the principle of tarāḍī (mutual consent), and structural scholars, who oppose the practice by highlighting the sacredness and ethical objectives of marriage, particularly the protection of women, children, and the family institution. This article argues that the ensuing debate reflects an epistemological dialectic between formal legality and social legitimacy, while also demonstrating that Islamic law in the Indonesian context serves a dual function: preserving the continuity of the fiqh tradition and simultaneously acting as a dynamic site of change responsive to contemporary socio-cultural developments. [Nikah misyār merupakan salah satu praktik perkawinan paling kontroversial dalam wacana hukum Islam kontemporer karena, meskipun sah secara formal, praktik ini menimbulkan problematika sosial dan etis. Studi-studi terdahulu cenderung berfokus pada aspek legalitas fikih, regulasi negara, atau respons publik. Artikel ini berupaya mengisi kekosongan tersebut dengan menelaah bagaimana para ulama yang berafiliasi dengan Nahdlatul Ulama (NU) di Jawa Timur menegosiasikan teks normatif, tradisi keilmuan, dan realitas sosial dalam merespons fenomena ini. Penelitian ini menggunakan pendekatan sosio-legal melalui wawancara semi-terstruktur terhadap 14 informan kunci, observasi non-partisipan di empat komunitas perumahan di Surabaya, serta analisis dokumen berupa kitab-kitab fikih dan arsip pernikahan. Temuan penelitian mengidentifikasi tiga model utama praktik nikah misyār di Surabaya: sebagai strategi perempuan karier, sebagai perkawinan jangka pendek untuk menghindari kerumitan birokrasi, dan sebagai perkawinan transnasional dengan laki-laki asing. Motivasi dari praktik ini melampaui sekadar pemenuhan biologis, melainkan juga mencakup dimensi ekonomi, sosial, dan budaya. Respons para ulama NU mengerucut pada dua arus utama: ulama kultural yang menekankan validitas kontraktual berbasis prinsip saling rida, dan ulama struktural yang menolak praktik ini dengan menekankan kesakralan serta tujuan etis perkawinan, khususnya perlindungan terhadap perempuan, anak, dan institusi keluarga. Artikel ini berargumen bahwa perdebatan tersebut mencerminkan dialektika epistemologis antara legalitas formal dan legitimasi sosial, sekaligus menunjukkan bahwa hukum Islam dalam konteks Indonesia berfungsi ganda: melanjutkan kesinambungan tradisi fikih sekaligus menjadi arena perubahan yang responsif terhadap dinamika sosial-budaya kontemporer.]